Effect of positive end-expiratory pressure on gastric insufflation during induction of anaesthesia when using pressure-controlled ventilation via a face mask: A randomised controlled trial. Issue 9 (September 2019) - Cajander, Per; Edmark, Lennart; Ahlstrand, Rebecca; Magnuson, Anders; de Leon, Alex
Abstract : BACKGROUND: Face mask ventilation (FMV) during induction of anaesthesia is associated with risk of gastric insufflation that may lead to gastric regurgitation and pulmonary aspiration. A continuous positive airway pressure (CPAP) has been shown to reduce gastric regurgitation. We therefore hypothesised that CPAP followed by FMV with positive end-expiratory pressure (PEEP) during induction of anaesthesia would reduce the risk of gastric insufflation. OBJECTIVE: The primary aim was to compare the incidence of gastric insufflation during FMV with a fixed PEEP level or zero PEEP (ZEEP) after anaesthesia induction. A secondary aim was to investigate the effects of FMV with or without PEEP on upper oesophageal sphincter (UES), oesophageal body and lower oesophageal sphincter (LES) pressures. DESIGN: A randomised controlled trial. SETTING: Single centre, Department of Anaesthesia and Intensive Care, Örebro University Hospital, Sweden. PARTICIPANTS: Thirty healthy volunteers. INTERVENTIONS: Pre-oxygenation without or with CPAP 10 cmH2 O, followed by pressure-controlled FMV with either ZEEP or PEEP 10 cmH2 O after anaesthesia induction. MAIN OUTCOME MEASURES: A combined impedance/manometry catheter was used to detect the presence of gas and to measure oesophageal pressures. The primary outcome measure was the cumulative incidence of gastric insufflation, defined as a sudden anterograde increase in impedance of more than 1 kΩ over the LES. Secondary outcome measures were UES, oesophageal body and LES pressures. RESULTS: The cumulative incidence of gastric insufflation related to peak inspiratory pressure (PIP), was significantly higher in the PEEP group compared with the ZEEP group (log-rank test P  < 0.01). When PIP reached 30 cmH2 O, 13 out of 15 in the PEEP group compared with five out of 15 had shown gastric insufflation. There was a significant reduction of oesophageal sphincter pressures within groups comparing pre-oxygenation to after anaesthesia induction, but there were no significant differences in oesophageal sphincter pressures related to the level of PEEP. CONCLUSION: Contrary to the primary hypothesis, with increasing PIP the tested PEEP level did not protect against but facilitated gastric insufflation during FMV. This result suggests that PEEP should be used with caution after anaesthesia induction during FMV, whereas CPAP during pre-oxygenation seems to be safe. TRIAL REGISTRATION: ClinicalTrials.gov, identifier: NCT02238691.